2021
DOI: 10.1186/s12966-021-01146-3
|View full text |Cite
|
Sign up to set email alerts
|

International evaluation of the Microscale Audit of Pedestrian Streetscapes (MAPS) Global instrument: comparative assessment between local and remote online observers

Abstract: Objectives The use of online imagery by non-local observers to conduct remote, centralized collection of streetscape audit data in international studies has the potential to enhance efficiency of collection and comparability of such data for research on built environments and health. The objectives of the study were to measure (1) the consistency in responses between local in-field observers and non-local remote online observers and (2) the reliability between in-country online observers and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…For the high SES, this study found that there was no correlation between walking, moderate PA, and vigorous PA with the characteristics of the built environment. Lots of literature mainly studies the correlation between the built environment and physical activity [67,68] and supports this relationship, but according to ArcGIS and other measures, for neither SES, the elderly could obtain the same benefits from the built environment of "fitting physical activity" [27,69].…”
Section: Discussionmentioning
confidence: 99%
“…For the high SES, this study found that there was no correlation between walking, moderate PA, and vigorous PA with the characteristics of the built environment. Lots of literature mainly studies the correlation between the built environment and physical activity [67,68] and supports this relationship, but according to ArcGIS and other measures, for neither SES, the elderly could obtain the same benefits from the built environment of "fitting physical activity" [27,69].…”
Section: Discussionmentioning
confidence: 99%
“…( Queralt et al, 2021 ) Fox et al reported a significant association between measurements of local on-street observations conducted in the same five cities and remote online observations conducted in the United States. ( Fox et al, 2021 ) Thus, online observations using MAPS-Global have been confirmed to be highly reliable.…”
Section: Introductionmentioning
confidence: 77%
“…( Cain et al, 2018 ) In a study of five cities worldwide (Melbourne, Ghent, Curitiba, Hong Kong, and Valencia) using MAPS-Global, the inter-rater reliability of on-street, live and online, and local and remote online observations was tested and found to have moderate to excellent reliability for all data collection modes. ( Cain et al, 2018 , Fox et al, 2021 , Queralt et al, 2021 , Vanwolleghem et al, 2016 ) Queralt et al conducted a study using MAPS-Global in the above five cities and confirmed the high reliability of almost all the items for both on-street and online observations. However, aesthetic and social environment variables had the lowest overall reliability values, although they were still in the “good to excellent” category.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The MAPS tool for the neighbourhood environment audit at the streetscape level has been deployed successfully in several countries (Fox et al, 2021). However, in our knowledge it is the first time it has been employed in the GCC.…”
Section: Limits and Outlookmentioning
confidence: 99%